2020
DOI: 10.1186/s13063-020-4171-0
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol for a randomized controlled trial: prophylactic swallowing exercises in head-and-neck cancer patients treated with (chemo)radiotherapy (PRESTO trial)

Abstract: Background: Dysphagia is a common and serious complication after (chemo)radiotherapy (CRT) for head-and-neck cancer (HNC) patients. Prophylactic swallowing exercises (PSE) can have a significantly positive effect on posttreatment swallowing function. However, low adherence rates are a key issue in undermining this positive effect. This current randomized trial will investigate the effect of adherence-improving measures on patients' swallowing function, adherence and quality of life (QOL). Methods: This ongoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 57 publications
(77 reference statements)
0
37
0
1
Order By: Relevance
“…Duration of the treatment block was defined in 15 studies [ 14 16 , 21 27 , 30 32 , 36 , 37 ]. The most common recommendation was the duration of radiotherapy [ 15 , 16 , 21 , 22 , 27 , 30 , 31 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Duration of the treatment block was defined in 15 studies [ 14 16 , 21 27 , 30 32 , 36 , 37 ]. The most common recommendation was the duration of radiotherapy [ 15 , 16 , 21 , 22 , 27 , 30 , 31 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only one article [ 37 ] compared prehabilitation using the Shaker versus the Mendelsohn maneuver and found superior results in the Shaker group, including improvements in hyoid bone movement, thyrohyoid shortening, upper esophageal sphincter opening, reduced aspiration score and reduced feeding tube rates. Four articles included in the present review were proposed protocols or feasibility studies reporting no outcomes [ 22 , 26 , 29 , 32 ]. Of the remaining studies that reported on outcomes, 20 studies reported on short term outcomes (12 months or less), while five reported on outcomes beyond 12 months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since these reviews, a few randomized clinical trials of swallowing exercise interventions have been published and/or are currently underway each with differing foci. These include a theory-based behavior change approach to swallowing exercise interventions [ 286 ], prophylactic exercises delivered via different methods including home-based, home-based with counseling via an App, face-to-face therapy [ 287 ], and swallowing exercises with respiratory muscle training randomized to two groups of patients; before CRT or immediately after treatment completion [ 288 ].…”
Section: Oropharyngeal Dysphagia Treatment In Head and Neck Cancermentioning
confidence: 99%
“…2 Clinical studies have reported that 50%-60% of patients undergoing CRT for HNC present with significant postintervention dysphagia. 52 While studies have sought to characterize swallowing deficits exhibited post-CRT, an explanation of the dichotomous presence or absence of deficits is not forthcoming. Our study identified a significant increase in postswallow inhale events for rats that underwent CRT.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%